How my sons lost their Tagalog - Pimentel, Benjamin 1964- (Quezon City Ateneo de Manila University Press, 2013)
Personal essays on Philippine social life, politics, and Filipino in America.
In English and Tagalog.
Keywords: Philippines -- Social life and customs; Filipino Americans -- Social life and customs; National characteristics, Philippine; Philippines -- Politics and government